Achievements and Issues Strategic of Sustainable Development Goals of Yahukimo Regency - Gilang Adinugroho (Sustainability (STPP) Theory, Practice and Policy, 2021)
Yahukimo Regency experiences regional development developments every year but is still a disadvantaged area. There needs to be an acceleration of development to reduce the lag gap. However, development needs to pay attention to the environment and sustainability. SDG's are one of the instruments to mainstream sustainable development in planning documents. The achievement of SDG's in Yahukimo Regency has reached 5, 55 have not been achieved and 146 there is no data. Strategic issues for sustainable development include poverty, infrastructure, human resources, supporting facilities and macroeconomics. Sustainable development should be the basis in the planning document. This is to reduce the negative impact of development activities.